Analisis Keterampilan Manajerial dalam Pengambilan Keputusan: Peran Motivasi dan Komunikasi dalam Organisasi - Dipoatmodjo, Tenri Sayu Puspitaningsih (Journal Management & Economics Review (JUMPER), 2024)
Decision-making is a vital process that has a direct impact on organizational performance, and is strongly influenced by an individual's ability to integrate interpersonal skills, personal motivation, and communication effectiveness. This research reviews the determination of organizational behavior and decision making: analysis of skills, motivation and communication, human resource management literature. The purpose of writing this article is to build hypotheses of influence between variables that will be used in further research. The results of this research literature are: 1) Effect of Organizational Behavior on Organizational Behavior; 2) The Effect of Motivation on Organizational Behavior; 3) The Effect of Communication on Organizational Behavior; 4) Effect of Organizational Behavior on Decision Making; 5) Effect of Motivation on Decision Making; 6) Effect of Communication on Decision Making; and 7) Effect of Organizational Behavior on Decision Making.